Điện thoại thông minh thúc đẩy tiếp cận tín dụng của hộ gia đình ở Tây Bắc, Việt Nam: Hàm ý chính sách ứng dụng công nghệ số trong thúc đẩy tài chính toàn diện ở nông thôn - Đỗ Xuân , Luận (JOURNAL OF ASIAN BUSINESS AND ECONOMIC STUDIES, 2020)
he study aims to test the hypothesis that smartphone ownership increases rural households' accessibility to bank credit. The study employs an instrumental variable probit (IVprobit) to analyze data collected through direct interviews with 539 rural households in Northwestern Vietnam. Results show that smartphone ownership is positively correlated with the access to formal credit of rural households. Smartphones help people access to bank credit information, loan terms, and lending conditions conveniently. Smartphones also help rural people to grasp business information to enhance their knowledge and competencies in using loans effectively. The research results imply that the development of smartphone applications to supply credit and other banking services in rural mountainous areas is potential in order to reduce transaction costs and collateral dependence. However, possible transaction risks should be minimized to increase users’ trust. In addition, it is necessary to improve the competency of rural people in applying digital technologies in their production and business activities.
Keywords: Digital technology; Smartphone; Rural households; Northwestern Vietnam; Credit